2022
DOI: 10.1002/lol2.10243
|View full text |Cite
|
Sign up to set email alerts
|

Thicker shells reduce copepod grazing on diatoms

Abstract: The diatom frustule provides partial protection against copepod grazing. Whether the defense is due to the cells being de‐selected or handled for so long that the grazers lose time for foraging is unknown. The mechanism has implications for the population dynamics of both defended and co‐occurring, undefended nutrient competitors. We use video‐observations to demonstrate that thick‐shelled diatoms captured by the copepod Temora longicornis were rejected more frequently than thin‐shelled diatoms, irrespective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…Thus, responding to predator presence by increasing toxin production is still an adequate response by P. seriata , and presumably also other toxic phytoplankton, in mixed prey suspensions. This is similar to the effect of prey concentration on the rejection frequency of three species of centric diatoms that thicken their shells in response to copepod cues [35]. A higher prey concentration increased the odds of rejection in both defended and undefended cells, but the relative increased odds of rejection in defended cells remained similar.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, responding to predator presence by increasing toxin production is still an adequate response by P. seriata , and presumably also other toxic phytoplankton, in mixed prey suspensions. This is similar to the effect of prey concentration on the rejection frequency of three species of centric diatoms that thicken their shells in response to copepod cues [35]. A higher prey concentration increased the odds of rejection in both defended and undefended cells, but the relative increased odds of rejection in defended cells remained similar.…”
Section: Discussionsupporting
confidence: 74%
“…Foraging on small prey leaves less room for prey selection (Figs. 6, 7A), consistent with the observation that copepods are less selective when feeding on small than when feeding on large prey (Ryderheim et al 2022a) and that copepods feeding on small prey require higher food densities (Frost 1972;Kiørboe et al 2018). In addition, the impact of increased handling times on ingestion is relatively higher with smaller prey, despite the higher probability to ingest.…”
Section: Is Prey Handling and Prey Selection Limiting Consumption Rates?supporting
confidence: 81%
“…However, prey‐handling times may vary between copepods with different feeding modes and are in addition influenced by several prey‐related factors. Generally, larger prey take longer to handle and ingest (Rao and Kumar 2002; Tiselius et al 2013; Gonçalves et al 2014; Ryderheim et al 2022 b ), and more recently it was found that diatoms with thicker shells are handled for a significantly longer time than those with thin shells (Ryderheim et al 2022 a ). Also, copepods are known to be very selective feeders (Teegarden 1999; Leitão et al 2018) and may handle but reject a large fraction of captured prey, which may thus further detract from the time available for searching new prey (Jeschke et al 2002).…”
mentioning
confidence: 99%
“…However, the extent to which these variables were reported in original studies varied, and our analyses focus on those variables most often clearly described by study authors. Particulate Si:C ratios in diatoms were a covariate of interest, as diatom silicification is highly plastic and significantly modifies copepod-diatom interactions (Grønning & Kiørboe, 2020;Ryderheim et al, 2022); however, this information was notably not reported in studies in our dataset.…”
Section: Below)mentioning
confidence: 74%